Land speculation and intensification at the frontier: a seeming paradox in the Colombian savanna - Smith, J.; Cadavid Herrera, JV; Rincón Castillo, A.; Vera, Raúl R. (International Center for Tropical Agriculture, 1994)
Frontier areas in Latin America have been characterized by land speculation, abandonment and exploitation. This paper analyzes a frontier cattle ranching area in the savanna where intensification has occurred in spite of land speculation. A whole farm livestock production model is used to quantify the determinants of intensification. Results show that land speculation has simultaneously increased the profitability of cattle ranching while slowing down intensification and impeding the adoption of sustainable practices. Intensification occurred because the production gains offered by improved pastures over native grasses were large enough to overcome the negative effect of land speculation on intensification. By contrast, in the Amazon, improved technologies have to overcome the high fertility of newly deforested land. Thus, technology, land speculation and characteristics of the resource base interact in a complex way to determine the speed and nature of intensification